IMPLEMENTASI COMPUTATIONAL THINKING DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Megawati, Annas Tasya; Sholihah , Mona; Limiansih, Kintan (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2023)
ABSTRAK The implementation of computational thinking in learning in elementary schools is still a challenge for education, especially educators and students in schools. Teachers must be able to design learning by integrating computational thinking so that the learning process is more meaningful while students are required to be able to solve problems with logical, sequential, and effective steps. This study aims to provide an overview of the application of computational thinking in learning mathematics and to determine the effect of applying computational thinking in learning mathematics in Grade IV Elementary School. The research method uses a single one shot case study design. The research subjects consisted of 21 people in class IV of Elementary School Muhammadiyah Siraman Wonosari in the 2022/2023 academic year. This research took place during one meeting, the implementation of which was in accordance with the implementation plan for learning fraction material. This research produced some data, namely (a) Data analysis of student learning outcomes reached 83.7. (b) Analysis of student activity data reached a percentage of 80.42%. (c) Data analysis on the ability of teachers to obtain an average score of 3.67 (good criterion). (d) Analysis of student response data to learning to get positive results by reaching 96.19%. Keywords: computational thinking, learning mathematics, elementary school ABTRACT Implementasi berpikir komputasi dalam pembelajaran di sekolah dasar masih menjadi tantangan bagi pendidikan khususnya pendidik dan peserta didik di sekolah. Guru harus mampu merancang pembelajaran dengan mengintegrasikan berpikir komputasi agar proses belajar lebih bermakna sedangkan peserta didik dituntut untuk dapat menyelesaikan permasalahan dengan langkah-langkah yang logis, urut, dan efektif. Penelitian ini bertujuan untuk memberikan gambaran penerapan berpikir komputasi dalam pembelajaran matematika dan mengetahui pengaruh penerapan berpikir komputasi dalam pembelajaran matematika di Sekolah Dasar Kelas IV. Metode penelitian menggunakan jenis penelitian kualitatif. Subjek penelitian terdiri dari 21 orang di kelas IV Sekolah Dasar Muhammadiyah Siraman Wonosari pada tahun ajaran 2022/2023. Penelitian ini berlangsung selama satu kali pertemuan yang pelaksanaannya sesuai dengan rencana pelaksanaan pembelajaran materi bilangan pecahan. Penelitian ini menghasilkan beberapa data yaitu (a) Analisis data hasil belajar siswa mencapai 83,7. (b) Analisis data aktivitas siswa mencapai persentase sebesar 80,42% . (c) Analisis data kemampuan guru memperoleh skor rata-rata 3,67 (kreteria baik). (d) Analsis data respon siswa terhadap pembebelajaran mendapatkan hasil positif dengan mencapai 96,19%. Keywords: berpikir komputasi, pembelajaran matematika, sekolah dasar